Sex-and sport related differences in the personality traits students in volleyball, basketball and judo athletes - Obminski, Z.; Mroczkowska, H.; Jagiello, M.; Litwiniuk, A. (Physical Education of Students, 2020)
Background and Study Aim. Psychology is a very important field of knowledge in every area of human life, and personality and temperament have a large impact on the quality of human life, including mental and physical health, and indirectly on the results achieved in elite sport. The purpose of the study was to verify the assumption that there are differences in the psychological profile of professional sportsman students depending on the gender and type of sports discipline. Material and methods. The research covered athletes of both sexes belonging to academic sports clubs practicing volleyball, basketball and judo. The size of each of the six groups was 24 people. Standardized psychological tests were used to determine the levels of selected personality and temperamental traits: trait anxiety, neuroticism, extraversion, briskness, perseveration, sensory sensitivity, emotional reactivity, endurance, activity, and six components of aggressiveness: physical aggressiveness, verbal aggressiveness, indirect aggressiveness, negativism, suspiciousness, resentment, irritability, overall and guilty sense. Two-way analysis of variance (sex * sport) was used to assess the differences between the groups. Results. Women showed higher trait anxiety, extraversion, perseveration, emotional reactivity results and lower physical aggressiveness levels compared to men. Basketball practitioners had the lowest levels of aggressiveness components, and the highest levels of briskness. Conclusions. The results suggest that the psychological profile of women participating in competitive sports may account for a higher emotional cost than men in terms of competition and failure. This fact should be taken into account by the coaches of female sports teams. The differences between sports may be due to the different structure of the task.